Ligand-conjugated multiwalled carbon nanotubes for cancer targeted drug delivery - Thakur, Chanchal Kiran; Karthikeyan, Chandrabose; Ashby, Charles R.; Neupane, Rabin; Singh, Vishal; Babu, R. Jayachandra; Narayana Moorthy, N. S. Hari; Tiwari, Amit K. (Frontiers in Pharmacology, 2024)
Multiwalled carbon nanotubes (MWCNTs) are at the forefront of nanotechnologybased advancements in cancer therapy, particularly in the field of targeted drug delivery. The nanotubes are characterized by their concentric graphene layers, which give them outstanding structural strength. They can deliver substantial doses of therapeutic agents, potentially reducing treatment frequency and improving patient compliance. MWCNTs' diminutive size and modifiable surface enable them to have a high drug loading capacity and penetrate biological barriers. As a result of the extensive research on these nanomaterials, they have been studied extensively as synthetic and chemically functionalized molecules, which can be combined with various ligands (such as folic acid, antibodies, peptides, mannose, galactose, polymers) and linkers, and to deliver anticancer drugs, including but not limited to paclitaxel, docetaxel, cisplatin, doxorubicin, tamoxifen, methotrexate, quercetin and others, to cancer cells. This functionalization facilitates selective targeting of cancer cells, as these ligands bind to specific receptors overexpressed in tumor cells. By sparing non-cancerous cells and delivering the therapeutic payload precisely to cancer cells, this therapeutic payload delivery ability reduces chemotherapy systemic toxicity.There is great potential for MWCNTs to be used as targeted delivery systems for drugs. In this review, we discuss techniques for functionalizing and conjugating MWCNTs to drugs using natural and biomacromolecular linkers, which can bind to the cancer cells' receptors/biomolecules. Using MWCNTs to administer cancer drugs is a transformative approach to cancer treatment that combines nanotechnology and pharmacotherapy. It is an exciting and rich field of research to explore and optimize MWCNTs for drug delivery purposes, which could result in significant benefits for cancer patients.